2006
DOI: 10.4012/dmj.25.75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adhesive Primer Developed Exclusively for Heat-curing Resin on Adhesive Strength between Plastic Artificial Tooth and Acrylic Denture Base Resin

Abstract: Despite progress in the development of denture base resin and artificial tooth materials, dental clinics are still plagued with artificial teeth falling off the denture base -due to poor bond strength -after denture delivery. Against this background, this study sought to examine the effect and durability of an adhesive primer developed exclusively for heat-curing resin on the adhesive strength of heat-curing denture base acrylic resin to plastic artificial tooth. Test specimens were divided into four groups ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…In turn, crack initiation and propagation at the interface are likely to occur, which may affect the bond strength between denture teeth and denture base resins. 14,15,27,28,41,44 5000 cycles between 5 and 55 8C were selected, as this has been developed a standard procedure for artificial ageing. It has to be mentioned, however, that no studies have adequately shown a correlation of the number of thermocycles to months or years of clinical service.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In turn, crack initiation and propagation at the interface are likely to occur, which may affect the bond strength between denture teeth and denture base resins. 14,15,27,28,41,44 5000 cycles between 5 and 55 8C were selected, as this has been developed a standard procedure for artificial ageing. It has to be mentioned, however, that no studies have adequately shown a correlation of the number of thermocycles to months or years of clinical service.…”
Section: Discussionmentioning
confidence: 99%
“…22 In contrast, other authors used shear, compressive or peel tests to assess the bond strength between denture teeth and denture base resins. 10,11,23,[38][39][40][41][42][43][44][45][46][47] It is speculated that, under clinical conditions, the force direction leading to debonding of denture teeth is a combination of tensile and shear forces. This can, however, hardly be simulated 1:1 in an in vitro experiment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the application of non-polymerizing solvents like dichloromethane, chloroform and adhesive bonding agent seem to enhance the bond strength between denture base resin and acrylic resin teeth [8][9][10][11][12][13]. Adeyemi et al, [12] stated that the chemical bonding between teeth and the polymer-monomer dough occurs through absorption of monomer by the surface layers of teeth.…”
Section: Introductionmentioning
confidence: 99%